Wireless sensor technology for structural health monitoring of historical masonry structures - Aguilar, Rafael (2009)
For the preservation of monuments and existent structures the Health Monitoring and the Damage Identification play an important role. Nowadays the developments on Micro-Electro-Mechanical Systems (MEMS) incorporated with Wireless Sensor Networks (WSN) are attractive to monitoring the behavior of structures, particularly, in rather complex masonry structures where a significant number of sensors are required to understand the structural behavior. With this purpose the University of Minho started broad researches which tend to apply this novel technology in the civil engineering field. In this work only commercial platforms available were used. Modal analysis of a laboratory specimen was performed using conventional and wireless based equipments.